(untitled) (Research, Society and Development, 2021)
The physiotherapist works in auxiliary obstetrics and prepares the woman for labor and delivery. Therefore, the aim of this study was to identify the resources that help physical therapists in managing pain during labor. This is a literature review with a qualitative approach, including studies published between 2016 and 2021, in Portuguese and English, in the databases: PubMed, PEDro (Physiotherapy Evidence Database) and Academic Google. The articles included were all of an experimental nature, carried out in humans, and finally 13 articles that met the inclusion criteria were selected. Resources found in the literature for pain management during labor were: hydrotherapy (hot bath or immersion) (23.1%), acupressure (23.1%), transcutaneous electrical nerve stimulation (TENS) (23.1%), massage (30.7%), thermotherapy (cold and/or heat) (15.3%) and breathing exercises (7.7%). It was concluded that the resources found show to be effective for pain control during labor and knowledge about them is necessary to better assist the parturients in this process.